The Impact of Remittances on Household Welfare: Evidence from Kyrgyzstan - Turarova, Naziya (Nazarbayev University School of Sciences and Humanities, 2020)
In this paper I study the impact of remittances on household welfare in Kyrgyzstan. I deploy asset indices calculated using Principal Component Analysis and asset accumulation over four years (2010-2013) to measure the average effect of remittances on household well-being. The Propensity Score matching method is applied to address the self-selection to receive remittances and the 2010 data on asset holdings is used to add the pre-treatment information on assets. The study finds that remittances have a negative impact on consumer asset holdings and the accumulation of productive assets over four year-period. Keywords: remittances; Propensity Score Matching; Principal Component Analysis.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics